2006
DOI: 10.4319/lo.2006.51.4.1637
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of stable isotopes and fossil pigments in surface sediments of Alaskan coastal lakes: Constraints on quantitative estimates of past salmon abundance

Abstract: We quantified spatial patterns of stable isotopes of N and C (d 15 N, d 13 C) and fossil pigment concentrations in the uppermost 10 mm of sediment (,10 yr) from 74 profundal locations and three spawning-stream discharge areas in Lake Nerka, southwest Alaska. Sediment d 15 N (4.3% 6 0.7%) and d 13 C (226.3% 61.2%) varied directly (d 15 N ) or inversely (d 13 C) with water column depth, whereas concentrations of most fossil pigments from algae were negatively correlated with depth. Sediment d 15 N and d 13 C wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…4). Analogous to limnological studies (Brock et al 2006), sedimentary concentrations of labile pigments (e.g. peridinin) were negatively related to depth (R 2 00.13, P 00.18).…”
Section: Interpretation Of Fjord Sedimentary Recordsmentioning
confidence: 90%
“…4). Analogous to limnological studies (Brock et al 2006), sedimentary concentrations of labile pigments (e.g. peridinin) were negatively related to depth (R 2 00.13, P 00.18).…”
Section: Interpretation Of Fjord Sedimentary Recordsmentioning
confidence: 90%
“…5) to centuries (Figs. 3, 4), responses of algae to N and P supplements from salmon are much less predictable on annual timescales (e.g., Mitchell and Lamberti 2005;Brock et al 2006). In streams, disturbance of the benthic environment by spawning salmon may restrict algal growth (Mitchell and Lamberti 2005) and can facilitate MDN export to coastal lakes and estuaries (Chaloner et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, because past and present algal communities in these and other regional lakes are composed mainly of diatoms Brock et al 2006), and because the diatom indicator diatoxanthin was the predominant pigment (mean 40-90%) in all fossil carotenoid assemblages (P. R. Leavitt unpubl. data), only time series of diatoxanthin were used for subsequent statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, salmon move bioavailable nutrients out of streams. Brock et al (2006) found that sediments were slightly enriched with the stable isotope 15 N around the mouth of Pick Creek, evidence of local deposition and retention FIG. Schindler et al (2005) observed that productivity of Lake Nerka was responsive to changes in loading of salmon-derived nutrients.…”
Section: May 2007mentioning
confidence: 94%